Constraints to Small Firm and Medium’s Contribution to Economic Growth in Zambia - Matakala, Bridget Sikopo (Graduate School of Business (GSB), 2019)
Small to medium scale enterprises (SMEs) arguably drive economic growth and job creation in developing countries, but factors that hinder their growth are generic or specific to sectors and remain a crucial area of research. This study examines factors constraining SMEs from optimally contributing to economic growth of Zambia. The study answered the following research questions; what factors act as constraints for SMEs to contribute towards economic growth; how conducive are the policy and institutional infrastructure for the SMEs to operate efficiently and to establish whether the evidence presented by these factors are specific to Zambia or apply elsewhere. For research design, the study adopted the mixed research approach. Both quantitative and qualitative research approaches were implored in order to produce the findings outlined in this report. Simple random sampling was used to draw a total of 250 SMEs to which structured questionnaires were administered. Semi-structured interviews were also conducted with three major stakeholders. The study used the statistical package of social science (SPSS) to analyse the quantitative data while qualitative data was analysed thematically- by identifying key themes and summarizing related information under each theme- for perspectives around SMEs contribution to economic growth. The study findings identify internal and external factors that constrain SMEs from contributing efficiently to economic growth and these include; 1) poor access to finance, 2) competition, 3) lack/inadequate infrastructure, and 4) lack of skills and training and these are similar across regions and other countries. On the other hand, it was stated that the high cost of production (as a result of high/multiple taxes and tariffs) prevent SMEs ability to effectively contribute to economic growth. The findings further show that institutionalised efforts created to ensure the SMEs flourish contribute effectively to economic growth. However, the correlation between targeting and segmentation of the SMEs for funding key areas of economic activities is not clear. Results show that the major factors according to the survey were the failure to access finance as attested by 160 of the 250 respondents who put this as the biggest impediment in success of their business and 65 of the respondents gave high taxes as the factor affecting them the most. The rest of the respondents gave competition and the absence of appropriate infrastructure to support business growth as a reason for poor performance and contribution to wider economic growth. Additionally, the findings show that there is no significant relationship between internal and external constraining factors and enterprise contribution to economic growth. To ensure greater SME contribution to economic growth, this study emphasises government interventions in financial services and infrastructure development, clarity in the implementation of policy and institutional provisions, encouragement of SME value-chain and market linkages as well as creation of knowledge hubs.